2019
DOI: 10.1109/tcomm.2019.2920645
|View full text |Cite
|
Sign up to set email alerts
|

Sum Rate and Fairness Analysis for the MU-MIMO Downlink Under PSK Signalling: Interference Suppression vs Exploitation

Abstract: In this paper, we analyze the sum rate performance of multi-user multiple-input multiple-output (MU-MIMO) systems, with a finite constellation phase-shift keying (PSK) input alphabet. We analytically calculate and compare the achievable sum rate in three downlink transmission scenarios: 1) without precoding, 2) with zero forcing (ZF) precoding 3) with closed form constructive interference (CI) precoding technique. In light of this, new analytical expressions for the average sum rate are derived in the three ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…As an initial attempt, [147] conducts performance analysis of CI precoding when PSK signaling is considered, for the first time in the literature, where the achievable rate for each user and the total sum rate upper bound of CI transmission are derived.…”
Section: Fig 3: CI Region Characterization For Psk and Qam Constellamentioning
confidence: 99%
“…As an initial attempt, [147] conducts performance analysis of CI precoding when PSK signaling is considered, for the first time in the literature, where the achievable rate for each user and the total sum rate upper bound of CI transmission are derived.…”
Section: Fig 3: CI Region Characterization For Psk and Qam Constellamentioning
confidence: 99%
“…Once an end user makes a request for accessing service time, we initialize the procedure for fairness measurement. We introduce the concept of the fairness index from a Multi-User Multiple-Input-Multiple-Output (MU-MIMO) system [25]. The basic idea of the fairness index is balancing between fairness and throughput.…”
Section: ) Calculation Of the Fairness Indexmentioning
confidence: 99%
“…where Σ = D [5], [14]. It was shown that, the distribution of Ψ can be approximated to Gamma distribution, Ψ ∼ Γ (ν, θ) [5], [14].…”
Section: A Sep Of the Legitimate Usersmentioning
confidence: 99%
“…where Σ = D [5], [14]. It was shown that, the distribution of Ψ can be approximated to Gamma distribution, Ψ ∼ Γ (ν, θ) [5], [14]. Thus, the received SNR, γ d,k , can be approximated to General Gamma distribution Γ (ρ, ̺, κ) with ρ = 1 2 , ̺ = ν 2 and κ = θ 2 .…”
Section: A Sep Of the Legitimate Usersmentioning
confidence: 99%
See 1 more Smart Citation